Host Reaction of Some Local Tomato Varieties against Root Knot Nematode, Meloidogyne incognita (Kofoid and White) Chitwood - Mondal (Ghosh), Shanowly; Sardar, Bibek Singh; Gope, Amit; Mandi, Niranjan; Chakraborty, Gautam (Research Biotica, 2023)
An experiment was conducted for the investigations on screening on different local tomato varieties against RKN, Meloidogyne incognita under net house conditions during the year 2021-22. Out of thirty-five varieties only four (Abhimanyu, HY- Rocky, HY- 1276 and HY-Red Boar) were found to be moderately resistant to the nematode having root gall index between 2.1 to 3.0. Twenty-one varieties were found to be susceptible having root gall index between 3.1 to 4.0, but the remaining varieties were quite vulnerable to the nematode having root gall index between 4.1 to 5.0. Additionally, it was discovered that, in comparison to the other tomato types, Amlan and HY-3682 (Special) had the most gall infestation. All the varieties showed significant differences in their responses or reactions to root-knot nematodes from moderately resistant to vulnerable.